Penerapan Manajemen Resiko Untuk Meningkatkan Mutu Pendidikan Di Era Globalisasi - Maharani, Devina; Maharani, Irsyad; Setiawati, Merika (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The application of risk management in the education sector is a crucial strategy for improving quality and competitiveness in the era of globalization. The global era brings new challenges in the form of rapid technological change, ever-evolving competency demands, and increasingly fierce international competition. This paper reviews how risk management is applied in educational institutions to identify, evaluate, and control various potential risks that can hinder the achievement of educational quality. By using a structured approach to managing risks such as curriculum implementation delays, failure of learning technology devices, and resource mismatches, educational institutions can improve the effectiveness of the teaching and learning process and the quality of graduates. The implementation of appropriate risk management not only reduces negative impacts but also opens up opportunities for innovation and adjustments needed to meet global demands. Therefore, strengthening risk management is a key factor in maintaining the continuity of quality and relevance of education amidst global competition. This study presents basic concepts along with practical steps in implementing risk management in the world of modern education.